PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA SMP PADA MATERI SISTEM PERNAPASAN - Puspita Rani, Ria; Wahyuni, Sri; Rusdianto (Jurnal Biogenerasi, 2024)
This study aims to determine the effect of using interactive learning media on critical thinking skills of junior high school students on respiratory system material. The research was conducted at SMP N 2 Maesan. The research sample is class VIII students by taking two classes, each class totaling 20 students. Data collection methods using written tests totaling 10 multiple choice research instruments, consisting of interviews and documentation. The results of the study on each indicator of critical thinking skills the highest score was achieved on the interpretation indicator with a score of 80 in the experimental class. Meanwhile, the lowest score on analysis was 38 in the control class. The increase in students' critical thinking skills is due to the advantages of interactive learning media that are able to visualize abstract material, provide feedback to students, and present clear information, making it easier for students to understand the material explained. The conclusion of this study is that the use of interactive learning media on respiratory system material in learning has a significant effect on students' critical thinking skills.